Households' expectations and regional COVID-19 dynamics - Misina Cato; Tobias Schmidt (Deutsche Bundesbank, 2023)
In this paper we analyze how consumers in Germany updated expectations about inflation in response to the COVID-19 outbreak. We use a fixed effects model to estimate the effect of regional exposure to COVID-19 cases, the stringency of restriction measures and local unemployment rates on inflation expectations. We find that consumers who were locally more exposed to COVID-19 cases report higher inflation expectations. The relationship between the virus spread and inflation expectations is amplified if respondents live in high unemployment regions. We explain our findings through an information and experience channel. Information about the pandemic and its effects played an important role during the first wave of the pandemic. However, when attention to information diminishes, experience matters most. We document that negative personal (how severely the respondent was affected financially) and local experience (how severely the district was affected by COVID-19) are associated with higher inflation expectations and more pessimistic views with regard to unemployment, interest rates, house prices and the intention to spend. Our findings show that it is important to consider regional disparities when examining individual belief formation.
Keywords: E31; D14; D83; D84; G41; G51; 330; COVID-19 pandemic; inflation expectations; inflation disagreement; perceived severity of COVID-19; personal experience